Pengaruh Pelatihan Terhadap Pengetahuan tentang Gizi Buruk dan Inter-Professional Collaboration Petugas Puskesmas - Eny Pemilu Kusparlina (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2021)
The problem of nutritional status is very complex, requiring treatment involving a health nutritionist. The nutritional status of children is one of the important things to prepare a quality generation. Health education in the form of training is expected to be able to change the collaborative competences of health workers across professions. This study aims to analyze the effect of training on knowledge of health workers about malnutrition and cross-professional collaboration. The researcher used a mix-methods approach with triangulation techniques using a questionnaire for the qualitative stage by conducting content analysis, while in the quantitative stage the researcher used a pre-experimental design with a "one group pre and post test" design, then the data were analyzed using the Wilcoxon test and paired samples-t test. The results of the content analysis informed that the training had gone well and was able to increase the participants' knowledge. The statistical test results showed that the mean knowledge of nutrition before training was 4.50, while after training was 4.467. The results of the Wilcoxon test showed that the p value = 0.586 (> 0.05), so it can be interpreted that there is no difference in knowledge about nutrition between before and after training. Meanwhile, the average knowledge about collaboration before training was 8.75 and after training was 10.67. The results of the paired samples t-test showed a value of p = 0.008 (0,05), sehingga dapat diinterpretasikan bahwa tidak ada perbedaan pengetahuan tentang gizi antara sebelum dengan setelah pelatihan. Sedangkan rerata pengetahuan tentang kolaborasi sebelum pelatihan adalah 8,75 dan setelah pelatihan adalah 10,67. Hasil Wilcoxon test menunjukkan nilai p = 0,008 (